Proceedings of the 2023 CHI Conference on Human Factors in Computing Systems 2023
DOI: 10.1145/3544548.3581201
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Head Movements to Separate Head-Gaze and Head Gestures as Distinct Modes of Input

Abstract: Head movement is widely used as a uniform type of input for human-computer interaction. However, there are fundamental differences between head movements coupled with gaze in support of our visual system, and head movements performed as gestural expression. Both Head-Gaze and Head Gestures are of utility for interaction but difer in their afordances. To facilitate the treatment of Head-Gaze and Head Gestures as separate types of input, we developed HeadBoost as a novel classifer, achieving high accuracy in cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Besides hand-based input, head input has shown to be a promising input for disambiguation and refinement pointing for target selection, as the head affords hands-free fine control. In our previous work, we found that users have fine-grained over their head movement (∼0.3 degrees) [17]. Eye-head combination capitalises on the strengths of both modalities, with the eyes providing fast and precise input while head movements enable finer adjustments.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Besides hand-based input, head input has shown to be a promising input for disambiguation and refinement pointing for target selection, as the head affords hands-free fine control. In our previous work, we found that users have fine-grained over their head movement (∼0.3 degrees) [17]. Eye-head combination capitalises on the strengths of both modalities, with the eyes providing fast and precise input while head movements enable finer adjustments.…”
Section: Related Workmentioning
confidence: 99%
“…In our work, we build on the insights from BimodalGaze for automatic eye-head mode switching, and the potential of head movement classification from our previous work, HeadBoost [17]. The HeadBoost classifier addresses the challenge of correctly classifying between two fundamental types of head movements: gaze-driven head movement (Head-Gaze) and gestural head movement (Head Gesture).…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations